2019
DOI: 10.21203/rs.2.367/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytokine profiling reveals increased serum inflammatory cytokines in idiopathic choroidal neovascularization

Abstract: Background: The exact pathogenesis of idiopathic choroidal neovascularization (ICNV) remains unclear. Cytokine-mediated inflammation has been thought to be involved in the pathophysiology of ICNV. The purpose of this study was to investigate serum cytokine profiles in patients with ICNV and to explore the relationship between serum cytokine levels and ICNV severity. Methods: This case-control study was conducted in 32 ICNV patients and 30 healthy volunteers. Clinical and demographic information was obtained fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, we cannot rule out the possibility that some patients might have had a silent underlying inflammation or other conditions associated with the development of CNV. 34,35 Another limitation is the absence of a control group, showing the natural evolution of iCNV without treatment. However, at the time of patient inclusion, no comparative active treatments were approved.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot rule out the possibility that some patients might have had a silent underlying inflammation or other conditions associated with the development of CNV. 34,35 Another limitation is the absence of a control group, showing the natural evolution of iCNV without treatment. However, at the time of patient inclusion, no comparative active treatments were approved.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF drives the proliferation of many myeloid cell types, such as granulocytes, macrophages, and monocytes [28]. Previous reports have shown that GM-CSF is significantly elevated in the aqueous humor of CNV patients [6]. Immune/inflammation reaction occurs at this stage of CNV formation.…”
Section: Discussionmentioning
confidence: 98%
“…Although vascular endothelial growth factor (VEGF) is known as a potent proangiogenic factor [4], the exact pathogenesis of CNV is complex and has not been fully elucidated. Accumulating evidence has demonstrated inflammation to play an important role in the pathogenesis of CNV [5,6]. Guo et al [6] reported that serum inflammatory cytokines are significantly elevated and involved in idiopathic CNV patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation